Theory Derivation: Adaptation of a Contextual Model of Health Related Quality of Life to Rural Cancer Survivors - Leli Pedro (Rural Nurse Organization; Binghamton University, 2012)
For the growing population of cancer survivors, an obvious conceptual framework to guide the inquiry of health related quality of life (HRQOL) in rural cancer survivors has not emerged. In this paper, Walker and Avant's theory derivation procedures are used to adapt Ashing-Giwa's Contextual Model of HRQOL, the parent Model, to incorporate rurality into the Model's contextual dimensions. Rural cancer survivor relevant definitions and refinements are proposed for the macro (system) and micro (individual) level dimensions of the parent Model. This adaptation of the Ashing-Giwa HRQOL Model identifies concepts and components of a contextual model that must be included, measured, and accounted for to fully and deeply understand the HRQOL of rural cancer survivors.